Multigrid methods for cell‐centered discretizations on triangular meshes. Issue 4 (21st November 2012) - Salinas, P.; Rodrigo, C.; Gaspar, F. J.; Lisbona, F. J.
SUMMARY: This paper deals with the design of efficient multigrid methods for cell‐centered finite volume schemes on semi‐structured triangular grids. Appropriate novel smoothers are proposed for this type of discretizations, depending on the geometry of the grid. Because of the semi‐structured character of the mesh, on each structured patch, different smoothers can be considered. In this way, the multigrid method is constructed in a block‐wise form, and its global behavior will rely on the components on each block. Numerical experiments are presented to illustrate the good behavior of the proposed multigrid method. Copyright © 2012 John Wiley & Sons, Ltd.